Comparison of mechanical properties of recent and 400-year-old European larch wood - Enej Lipovec Zupanc; Gorazd Fajdiga; Miha Humar (Les)
Wood has been the leading building material throughout the history of mankind. Wood has several advantages over other construction materials, which also makes it one of the most promising materials of the future. The environmental aspect also plays a major role today, as wood is a natural, renewable resource whose processing is very energy-intensive. Due to its repeated and widespread use in construction, the prediction of mechanical properties and their change over time is also very well known, as the overall safety of all buildings also depends on it. Therefore, we compared the mechanical properties of fresh European larch (Larix decidua) and 400-year-old larch found in the Ruard manor house on the Stara Sava in Jesenice, where the renovation of the Upper Sava Museum is currently underway. In order to predict what will happen to the fresh wood over the long term, it is necessary to expose the wood to the same conditions, i.e. to change it with dynamic loads or material fatigue. The effect of aging on flexural strength has not been confirmed. Fatigue results show that old wood withstood about 18 times fewer load cycles than recent larch wood.